2011
DOI: 10.1353/mpq.2011.0016
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization as a Mediator of the Relation Between Facial Attractiveness and Internalizing Problems

Abstract: This study examined the relations between facial attractiveness, peer victimization, and internalizing problems in early adolescence. We hypothesized that experiences of peer victimization would partially mediate the relationship between attractiveness and internalizing problems. Ratings of attractiveness were obtained from standardized photographs of participants (93 girls, 82 boys). Teachers provided information regarding peer victimization experiences in sixth grade, and seventh grade teachers assessed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 113 publications
(153 reference statements)
0
4
0
2
Order By: Relevance
“…Turning to other child characteristics, cognitive functioning has been implicated in several problems, including conduct disorder (Boden et al 2010 ), and also linked with adolescent sexual behavior (Halpern et al 2000 ). Physical attractiveness may be related negatively to both peer relationship (Vannatta et al 2009 ) and internalizing problems (Rosen et al 2011 ), while romantic affiliations may serve as an additional stimulus to antisocial behavior over and above the influence of parenting and delinquent friends (Lonardo et al 2009 ). In turn, both physical attractiveness and romantic involvement are important for early sexual behavior (Zimmer-Gembeck et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Turning to other child characteristics, cognitive functioning has been implicated in several problems, including conduct disorder (Boden et al 2010 ), and also linked with adolescent sexual behavior (Halpern et al 2000 ). Physical attractiveness may be related negatively to both peer relationship (Vannatta et al 2009 ) and internalizing problems (Rosen et al 2011 ), while romantic affiliations may serve as an additional stimulus to antisocial behavior over and above the influence of parenting and delinquent friends (Lonardo et al 2009 ). In turn, both physical attractiveness and romantic involvement are important for early sexual behavior (Zimmer-Gembeck et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…For boys who look up to their popular classmates, frequent victimization by peers might represent concrete verification that they have not achieved this desired social position. Boys who are bullied may also infer that they possess undesirable attributes that are associated with being low in social power, such as submissiveness, physical unattractiveness, low athletic competence, and low social connectedness (Knack, Tsar, Vaillancourt, Hymel, & McDougall, 2012; Olweus, 1978; Rosen, Underwood, & Beron, 2011; Xie et al, 2006). The result is a painful contradiction to the social persona to which these adolescents aspire.…”
Section: Discussionmentioning
confidence: 99%
“…External characteristics, including facial attractiveness can become one of the factors that are associated with victimization and open reluctance of peers to interact. Rosen, Underwood & Beron (2011) conducted the study which revealed that less attractive teenagers became victims of their peers more often. It is assumed that high social competency can help protect less attractive children from https://dx.doi.org/10.15405/epsbs.2018.09.27 Corresponding Author: Alla A. Tvardovskaya Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 231 experiencing victimization, while a low social competency can serve as a risk factor for victimization even for the most attractive child.…”
Section: Problem Statementmentioning
confidence: 99%